2021
DOI: 10.3389/fvets.2021.718743
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of Splenic CD19+ B Cells in Mice Chronically Infected With Echinococcus granulosus sensu lato Protoscoleces

Abstract: Background: The larval stages of Echinococcus granulosus sensu lato (E. granulosus s.l) infection can alter B cell function and affect host anti-infective immunity, but the underlying mechanism remains unclear. The newly emerging immunometabolism highlights that several metabolites are key factors in determining the fate of immune cells, which provides a new insight for exploring how larval E. granulosus s.l. infection remodels B cell function. This study investigated the metabolomic profiles of B cells in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Furthermore, most DEGs related to inflammation and chemotaxis were significantly upregulated after infection. These results were consistent with our previous results that LPS stimulates infected B cells to produce both high levels of pro-inflammatory and anti-inflammatory cytokines ( 25 ).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, most DEGs related to inflammation and chemotaxis were significantly upregulated after infection. These results were consistent with our previous results that LPS stimulates infected B cells to produce both high levels of pro-inflammatory and anti-inflammatory cytokines ( 25 ).…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, intimate interaction between these genes of immune and metabolism was shown by co-expression network analysis. Correspondingly, our recent study also identified lots of differential metabolites associated with the functional differentiation and lipid metabolism in the splenic B cells post the parasitic infection ( 25 ). Overall, these findings primarily established the potential functional link of metabolic events and B cells' differentiation and function in response to the long-term infection of the larval E. granulosus .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations